Patient-reported outcomes following enzalutamide or placebo in men with non-metastatic, castration-resistant prostate cancer (PROSPER): a multicentre, randomised, double-blind, phase 3 trial. Issue 4 (April 2019) - Tombal, Bertrand; Saad, Fred; Penson, David; Hussain, Maha; Sternberg, Cora N; Morlock, Robert; Ramaswamy, Krishnan; Ivanescu, Cristina; Attard, Gerhardt
Summary: Background: In the PROSPER trial, enzalutamide significantly improved metastasis-free survival in patients with non-metastatic, castration-resistant prostate cancer. Here, we report the results of patient-reported outcomes of this study. Methods: In the randomised, double-blind, placebo-controlled, phase 3 PROSPER trial, done at 254 study sites worldwide, patients aged 18 years or older with non-metastatic, castration-resistant prostate cancer and a prostate-specific antigen doubling time of up to 10 months were randomly assigned (2:1) via an interactive voice web recognition system to receive oral enzalutamide (160 mg per day) or placebo. Randomisation was stratified by prostate-specific antigen doubling time and baseline use of a bone-targeting agent. The primary endpoint was metastasis-free survival, reported elsewhere. Secondary efficacy endpoints, reported here, were pain progression (assessed by the Brief Pain Inventory Short Form [BPI-SF] questionnaire) and health-related quality of life (assessed with the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire [EORTC QLQ-PR25], the EuroQoL 5-Dimensions 5-Levels health questionnaire visual analogue scale [EQ-5D-FL, EQ-VAS], and the Functional Assessment of Cancer Therapy-Prostate [FACT-P] questionnaires). Patients completed questionnaires at baseline, week 17, and every 16 weeks thereafter until treatment discontinuation. We used predefined questionnaire thresholds to identify clinically meaningful changes. Enrolment for PROSPER is complete and follow-up continues. This trial is registered withClinicalTrials.gov, numberNCT02003924 . Findings: Between Nov 26, 2013, and June 28, 2017, 1401 patients were enrolled and randomly assigned to receive enzalutamide (n=933) or placebo (n=468). Median follow-up was 18·5 months (IQR 10·7–29·2) in the enzalutamide group and 15·1 months (7·4–25·9) in the placebo group. Patient-reported outcome scores at baseline were similar between groups. Changes in least squares mean from baseline to week 97 favoured enzalutamide versus placebo for FACT-P social and family wellbeing (0·30 [95% CI −0·25 to 0·85] vs −0·64 [−1·51 to 0·24]; difference 0·94 [95% CI 0·02 to 1·85]; p=0·045) and disfavoured enzalutamide versus placebo for EORTC QLQ-PR25 hormonal treatment-related symptoms (1·55 [0·26 to 2·83) vs −1·83 [−3·86 to 0·20]; difference 3·38 [1·24 to 5·51]; p=0·0020); neither of these changes were clinically meaningful. No significant differences were observed between treatments for changes from baseline to week 97 in any other patient-reported outcome score. Time to clinically meaningful pain progression as assessed by BPI-SF pain severity was longer with enzalutamide than with placebo (median 36·83 months, [95% CI 34·69 to not reached [NR] vs NR; hazard ratio [HR] 0·75 [95% CI 0·57 to 0·97]; p=0·028); there was no significant difference for BPI-SF item 3 or pain interference. Time to clinically meaningful symptom worsening was longer with enzalutamide than with placebo for EORTC QLQ-PR25 urinary symptoms (median 36·86 months [95% CI 33·35 to NR] vs 25·86 [18·53 to 29·47]; HR 0·58 [95% CI 0·46 to 0·72]; p<0·0001) and bowel symptoms (33·15 [29·50 to NR] vs 25·89 [18·43 to 29·67]; 0·72 [0·59 to 0·89]; p=0·0018), and clinically meaningful health-related quality of life as assessed by FACT-P total score (22·11 [18·63 to 25·86] vs 18·43 [14·85–19·35]; 0·83 [0·69 to 0·99]; p=0·037), emotional wellbeing (36·73 [33·12 to 38·21] vs 29·47 [22·18 to 33·15]; 0·69 [0·55 to 0·86]; p=0·0008), and prostate cancer subscale (18·43 [14·85 to 18·66] vs 14·69 [11·07 to 16·20]; 0·79 [0·67 to 0·93]; p=0·0042), although there was no significant difference for other FACT-P scores. Time to clinically meaningful deterioration in EORTC QLQ-PR25 hormonal treatment-related symptoms was shorter with enzalutamide than with placebo (median 33·15 months [95% CI 29·60 to NR] vs 36·83 [29·47 to NR]; HR 1·29 [95% CI 1·02 to 1·63]; p=0·035). Time to deterioration of EQ-VAS was significantly longer for enzalutamide than for placebo (median 22·11 months [95% CI 18·46 to 25·66] vs 14·75 [11·07 to 18·17]; HR 0·75 [95% CI 0·63 to 0·90]; p=0·0013). Interpretation: Patients with non-metastatic, castration-resistant prostate cancer receiving enzalutamide had longer metastasis-free survival than did those who received placebo, while maintaining low pain levels and prostate cancer symptom burden and high health-related quality of life. Enzalutamide showed a clinical benefit by delaying pain progression, symptom worsening, and decrease in functional status, compared with placebo. These findings suggest that enzalutamide is a treatment option that should be discussed with patients presenting with high-risk, non- metastatic, castration-resistant prostate cancer. Funding: Astellas Pharma Inc, Medivation LLC (a Pfizer Company).